Funkcjonowanie dorosłych osób z niepełnosprawnością w Niemczech - Komorowska, Olga (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In Germany, the issue of prevention of social exclusion of people with disabilities is treated as the primary task of public policy. This article presents German solutions for adults with disabilities thanks to they are integrated into professional and social life. Among these solutions are own budget, job’s assistant, work in the professional workshop, support in accomodation, tax breaks, subsidies for rehabilitation equipment
Keywords: praca; osoby niepełnosprawne; wsparcie osób niepełnosprawnych; Niemcy; własny budżet; świadczenia dla osób niepełnosprawnych